Qualidade de vida no trabalho – estudo qualitativo com profissionais da Guarda Municipal de Belo Horizonte - Karine Teixeira Pedrosa (2020)
The Federal Constitution of 1988 determines, in Art. 144, that public security is a duty of the State, law and responsibility of all, having as its essential purpose the preservation of public order and the protection of people and property. With regard to the health and quality of life of workers in public safety, studies carried out in Brazil and other countries point out that factors arising from the organization and working conditions afflict the quality of life of these individuals, generating problems in social interaction, accidents and diseases. The quality of life at work comprises several aspects of the worker and organization relationship; such as: remuneration, working conditions, relationship with colleagues and management, time for leisure, career development opportunities and health. This study aimed to identify and analyze the concept of quality of life at work of the professionals of the Municipal Guard of Belo Horizonte and their perceptions of the factors that compromise it through the use of the methodology of focus groups. The Focal Group is part of the universe of qualitative researches intervening in a given reality through communication processes based on dialogue and the spontaneous participation of those involved, around central themes to which we want to explore. The main problems recognized by the interviewees were those related to institutional logistics, such as vehicles, personal protection equipment, vests, helmets and weapons, and the updating of legislation, such as the career plan or the GMBH Statute itself. It was found that listening to the "knowledge of the yard" can favor the understanding of the different aspects related to the quality of life at work that involve the professional practice of these workers, and can contribute to the improvement of health, satisfaction and professional performance.